Current overview of the Ecuadorian cultural wealth: a seed of talents and traditions - Author; Author; Author; Author; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In recent times there has been a lot of discussion about interculturality. This is good news, because it means that people are interested in the subject; however, it seems that there are still some points that must be clarified and certain aspects that can be better treated. This work aims to offer a contribution to the knowledge of interculturality and its validity in Ecuador. With a simple vocabulary, it faces the global problem in several of its most complex dimensions, so that readers, especially those who are participating in social organizations, have greater elements of judgment to understand the reality of our country. As its central issue cannot be treated in isolation, this work also addresses issues such as the Ecuadorian nation, ethnic and regional diversities, traditions, collective rights, and multinationality. He also makes some references to the international situation. It concludes with a consideration of national unity and the future of our country